Relationship between Family Support and Welfare Psychology of Prisoners During the Covid-19 Pandemic - Suhari; Yuni Darmawati; Rizka Yunita (Health and Technology Journal (HTechJ), 2023)
The high death rate due to Covid-19 does not only cause physical symptoms and illnesses but also has a major impact on well-being which includes mental health, including inmates at Class IIB Lumajang Penitentiary. The increasing number of inmates every year makes prison capacity overload. Low family support can lead to a person's psychological condition while serving a prison period, such as sadness, loneliness, and so on. The aim of the study was to determine the relationship between family support and the psychological well-being of inmates during the Covid 19 pandemic at Class IIB Lumajang Prison. The method used is correlation with cross-sectional design. The population in this study were all 529 inmates at Class IIB Lumajang prison in 2021 and the sample size was 228 respondents, using the simple random sampling technique. Retrieval of data using a questionnaire sheet family support and psychological well-being. The data obtained were then coded, scored, tabulated, and analyzed using the Spearman rank test. The results showed that most of the 120 respondents (52.6%) had good family support, and the psychological well-being of the majority of 135 respondents (59.2%) was in the sufficient category. The results of calculations with the Spearman rank test obtained p=0.000. Because p<0.05, there is a relationship between family support and the psychological well-being of prisoners during the Covid-19 pandemic at Class IIB Lumajang Prison in 2021. From the results of this study, it is hoped that respondents will be able to seek support from peers and prison staff to improve their psychological well-being and it is hoped that Class II B Lumajang prison officers will maximize their role to interact more deeply with prisoners.